2018
DOI: 10.1186/s12891-018-2287-0
|View full text |Cite
|
Sign up to set email alerts
|

Intra and interrater reliability and clinical feasibility of a simple measure of cervical movement sense in patients with neck pain

Abstract: BackgroundPattern tracing tasks can be used to assess cervical spine movement sense (CMS). A simple clinical measure of CMS (tracing fixed figure-of-eight (F8) and zigzag (ZZ) patterns with a head mounted laser) has been proposed and assessed in asymptomatic subjects. It is important to determine if examiner ratings of the traces are reliable and feasible for clinical use in those with neck pain. We therefore examined the intra- and inter-rater reliability of rating video recordings of the CMS tasks, and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…Subjects completed the questionnaires and then performed CMS testing in random order and according to an established method (Werner et al, 2018). Briefly, subjects sat on a chair with backrest, one metre away from a board where the F8 or ZZ pattern was attached.…”
Section: Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects completed the questionnaires and then performed CMS testing in random order and according to an established method (Werner et al, 2018). Briefly, subjects sat on a chair with backrest, one metre away from a board where the F8 or ZZ pattern was attached.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…A cost-effective and simple clinical alternative, where time and number of errors are recorded while tracing zigzag (ZZ) and figure of eight (F8) patterns with a head-affixed laser has been investigated in healthy asymptomatic and individuals with NP and shown to be reliable (Pereira et al , 2013, Werner et al , 2018. First indications of clinical feasibility were demonstrated but elaboration is needed (Werner et al, 2018). Accordingly, the primary aim of this study was to examine differences in CMS between age-and gender-matched individuals with NP and asymptomatic controls to determine suitable cut-off measures for clinical interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the foregoing, we showed that Seniors and Children needed to be slower (TT, Mean S, Acc, Dec) 5,14,32,33 to become as precise as Young and Old people (no significant differences for OS in all age-groups). The validity and reliability of the OS seems to be good when comparing patients with WAD with controls 21 and with patients with non-traumatic neck pain 30 . Even if we have calculated OS differently than Kristjansson et al (2004), this concept of analyzed is representative of the quality of the cervical sensorimotor status.…”
Section: Discussionmentioning
confidence: 96%
“…Because of their reliability, sensitivity and specificity 4,23 , the following specific parameters were computed for each kinematics variable: maximum/minimum rotational speed (Max S, Min S, in °s -1 ); average rotational speed (Mean S, in °s -1 ) and average rotational acceleration/deceleration (Acc, Dec, in °s -2 ). To assess the accuracy, we calculated overshoot (OS, in °) ( Fig.3) 30 . It was computed as the difference between peak rotation amplitude and stabilized mean rotation amplitude.…”
Section: Outcomes Measuresmentioning
confidence: 99%
“…For start and end positions, 50 frames were considered, 150 since the subjects were told to hold the position for two seconds. For following the Zigzag pattern (ZIZA) (Werner et al, 2018), data of the helmet without 162 differential signal to the trunk were considered, since the trunk sensors were hidden behind 163 the pattern for lighthouse visibility. Generalizability theory (G-theory) was applied to assess reliability, (Brennan, 2001).…”
Section: Procedures 134mentioning
confidence: 99%